Don’t Leave U.S. Behind - Janice Arellano (SAGE Open, 2015)
This article examines the pace at which Federal and State legislation were implemented to provide working parents and caregivers the ability to take time off for the birth or adoption of a child, to care for the elderly, sick or disabled family members, and others in need of care. Compared with many industrialized nations, the United States ranks alongside the least generous countries in terms of providing a balanced lifestyle between work and family life. For instance, the United States does not even provide national paid family leave. This article provides the history, purpose, and scope of the Family and Medical Leave Act, and later implementations of State programs. Furthermore, this article will present a brief survey of the paternal, maternal, and parental leave policies of other countries and will provide suggestions for changing existing federal policies to provide a more conducive family and work balance for employees.